Digitizing grey portions of e-governance. Issue 3 (21st August 2017) - Soni, Vivek; Dey, Prasanta Kumar; Anand, Rashmi; Malhotra, Charru; Banwet, Devinder Kumar
Abstract : Purpose: The purpose of this research paper is to assess e-governance efficacy in various sectors of India. The paper develops on Grey System Theory (GST) methodology and enlightens grey portions of e-governance in select sectors. Research study identifies few grey criteria which affect implementation of information and communication technology (ICT) applications to support sustainable e-governance. Such criteria are related to information security breaches, information technology (IT) policy implementation, investments and strategic advantages for the various sector developments. Design/methodology/approach: Considering "information" as a sensitive element to security for administration and part of dark portion to Indian economy, GST-based COmplex PRroportional ASsessment (COPRAS-G) method is adopted to assess the e-governance efficacy. The method provides flexible multicriteria decision-making (MCDM) approach to assess e-governance in prioritizing the sector alternatives of future strategic development. Priority order of select sectors is estimated, and COPRAS-G method is used in the research study to support decision-making on e-governance. Study compares ten major gross domestic product-dependent sectors based on few grey criteria. These criteria are chosen based on authors' perspective on this study and feedback received from government officials of district levels under the Digital India-training programme. To address the subjectivity that lies in e-governance grey areas of sector, criteria are also weighted using fuzzy scale. Later methodology-based results are presented to draw a strategic road map for strategic development of the country. Findings: On applying COPRAS-G method to predict pessimistic, optimistic and realistic scenarios of e-governance implementation across the ten sectors, high priory order in realistic scenario of results shows that implementation of ICT applications for e-governance should be in the sectors such as environment, climate change and in the railways. Industrial sector is also ranked as the preferred one over the other sectors on the basis of e-governance efficacy assessment. Research limitations/implications: Here COPRAS-G method is used as MCDM techniques. However, few other MCDM techniques such as GRA, DRSA, VIKOR, SMAA, SWARA and SAW can be also explored to outrank various Indian sectors to deal with subjectivity in decision-making. Practical implications: Implementation of ICT applications to support e-governance varies from sector to sector. ICT-based governance involves high degree of complexity in driving the operations for development of respective sectors. Therefore, government and policymakers need more flexibility to overcome present barriers of sector development. Such research can support decision-making where GST-based COPRAS-G method is able to capture and address the breaches of information security. Moreover, management concern for sector development has been presented on the basis of pessimistic, optimistic and realistic scenarios more precisely. Social implications: The results can provide guidance to the academicians, policymakers and public sectors highlighting various possible measures to handle the security breaches in multi-facet intention of sustainable development. The outcomes from MCDM framework can also help in drawing a rough trajectory of strategy, i.e. development of ICTs applications and e-governance process. Originality/value: This paper can supplement and act as the support for decision-making in conflicting situations on different flexible scenarios. Moreover, such work can synergize conflicting ideas of decision makers, academics and various other stakeholders of the Indian IT sector.